Effects of intracoelomic alfaxalone–dexmedetomidine on righting reflex in common garter snakes (Thamnophis sirtalis): preliminary data. (November 2020) - Chen, Kelly; Keating, Stephanie; Strahl-Heldreth, Danielle; Clark-Price, Stuart
Abstract: Objective: To evaluate the effect of dexmedetomidine on alfaxalone immobilization in snakes. Study design: Nonblinded, crossover study. Animals: A total of eight mature common garter snakes ( Thamnophis sirtalis ). Methods: Snakes were administered each of three treatments intracoelomically: alfaxalone (30 mg kg –1 ; treatment A), alfaxalone (30 mg kg –1 ) combined with dexmedetomidine (0.05 mg kg –1 ; treatment AD0.05); and alfaxalone (30 mg kg –1 ) combined with dexmedetomidine (0.10 mg kg –1 ; treatment AD0.10). A minimum of 10 days elapsed between experimental trials. Times to loss of righting reflex (LRR) and return of righting reflex (RRR) were recorded. Heart rate (HR) was recorded every 5 minutes throughout the period of LRR and averaged for each snake. Times to LRR and RRR, and mean HR in snakes that achieved LRR were reported. Results: LRR occurred in eight (100%), five (63%) and three (38%) snakes in treatments A, AD0.05 and AD0.10, respectively. For all treatments, time to LRR ranged 3–20 minutes. Median (range) times to RRR were 39 (30–46), 89 (62–128) and 77 (30–185) minutes for treatments A, AD0.05 and AD0.10, respectively. In animals where righting reflex was lost, mean HR was lower in all dexmedetomidine treatments compared with treatment A. Conclusions and clinical relevance: In this pilot study, alfaxalone resulted in reliable immobilization, whereas dexmedetomidine and alfaxalone combinations resulted in highly variable durations of immobilization with low HR in immobilized animals. For snakes that achieved LRR, the addition of dexmedetomidine (0.05 mg kg –1 ) to alfaxalone appeared to extend the period of immobilization compared with alfaxalone alone.